Looking Back and Looking Forward: Things I Wish I had Known Before Teaching in an Indigenous Community - Kim, Bora (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2023)
This essay relates the learning journey that I have been on as a non-Indigenous post-secondary educator teaching college courses in an Indigenous community and engaging in learning and unlearning about Indigenous Peoples and their history and world views in Canada. What I wish I had known before teaching college courses on reserve includes (1) more about Indigenous Peoples and their history in Canada, and (2) the four Rs of my responsibility as a non-Indigenous post-secondary educator. My journey of learning and unlearning has just begun and will be ongoing as Indigenous history is long and complicated, and Indigenous knowledges embrace contextual knowledge and relationships emerging from a specific Indigenous epistemology.